Description and toolkit for a research participant referral service - Nicholas Eberlein; Michael D. Musty; Jamie Roberts; Sierra Lindo; W. Schuyler Jones; Ranee Chatterjee (Journal of Clinical and Translational Science)
The success of clinical research studies depends on effective recruitment and retention of study participants, yet only a small fraction of patients engage in research studies, even in academic health systems. Increasing awareness of research opportunities and facilitating connections with clinical research study teams would help to improve the success of research programs. In this Special Communications, we describe the creation and evolution of and tools used for the My Research Partners Concierge Service (MRPcs) of an academic health system. The MRPcs provides a centralized point of contact or hub for patients and community members, as well as clinical research organizations and academic partners, who have research-related questions or interests. The MRPcs helps to connect the users of the service with relevant research study teams, personnel, or resources to facilitate their engagement in a clinical research program. Our experience with the MRPcs informs our recommendation that peer institutions organize similar research service hubs for their clinical research programs to help increase awareness of and participation in clinical research by the public and to help increase the success of research programs at fulfilling their ultimate goal of improving the health of their population.